Эквивалентное представление моделей сложных дискретных систем с помощью алгебры процессов - Нестеренко, Б.Б.; Новотарский, М.А. (Электронное моделирование, 2008)
The process algebra is considered which is on the parallel structure orientated description. The structures function with real working load. The basic concepts are determined for behavioral equivalence of models submitted by labeled transition systems. Definition is formed and the basic properties are stated for strong mutual model similarity. The direct and accelerated algorithms are developed for determination of strong mutual similarity on the basis of the received properties